MEDIA PEMBELAJARAN MAPAN (MATERI PERKALIAN DAN PEMBAGIAN PECAHAN) BERBASIS S.ID MICROSITE UNTUK SEKOLAH DASAR - Anwar, Afrah; Khotimah, Khusnul; Iksam, Iksam (Jurnal Visi Ilmu Pendidikan, 2025)
Technology has many benefits in the world of education, the researcher developed website-based learning media used s.id microsite to facilitated the learning process of students and teacher. This research aim to develop established learning media based on s.id microsite with DDD-E method. This research used Mapan material namely Fraction Multiplication       and  Division. This research was conducted at SD Negeri 007 Samarinda Ilir with a small group feasibility test of 5 students and a large group test of 22 students. The data was collected through questionnaires, interviews and documentation. This research used validation tests by linguists, material experts, media experts, student responses and teacher responses. The results showed that: (1) the media development process used the DDD-E model through 4 stages, namely decide, design, develop and evaluate. (2) the results of the feasibility test of teaching media by linguists, material and media validators obtained an average percentage of 89.34% with the decision that the media should be tested without revision. (3) the results of student responses showed a percentage of 90.23% and teachers showed a percentage of 93.69%. Based on data analysis, the researcher found that s.id microsite-based mapan learning media has advantages in linguistic aspects and usability. For the future researchers, the researcher suggest that have to conduct simulations to minimize constraints in research such as network availability, devices, learning flow on media and etc.